2013
DOI: 10.1039/c3ib40059j
|View full text |Cite
|
Sign up to set email alerts
|

Single cells from human primary colorectal tumors exhibit polyfunctional heterogeneity in secretions of ELR+ CXC chemokines

Abstract: Cancer is an inflammatory disease of tissue that is largely influenced by the interactions between multiple cell types, secreted factors, and signal transduction pathways. While single-cell sequencing continues to refine our understanding of the clonotypic heterogeneity within tumors, the complex interplay between genetic variations and non-genetic factors ultimately affects therapeutic outcome. Much has been learned through bulk studies of secreted factors in the tumor microenvironment, but the secretory beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The detection can then be accomplished by stopping the experiment at desired times and using secondary antibodies to detect the ligands captured at microspots in the experimental chamber. The finite element simulations executed in COMSOL to model diffusion of proteins (39,40) in the device confirmed that diffusion of proteins with the characteristic sizes matching those of the factors examined here is not distorted by pillars separating the chambers, with the diffusion profiles stable over prolonged time periods (SI Appendix, Fig. S2B).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The detection can then be accomplished by stopping the experiment at desired times and using secondary antibodies to detect the ligands captured at microspots in the experimental chamber. The finite element simulations executed in COMSOL to model diffusion of proteins (39,40) in the device confirmed that diffusion of proteins with the characteristic sizes matching those of the factors examined here is not distorted by pillars separating the chambers, with the diffusion profiles stable over prolonged time periods (SI Appendix, Fig. S2B).…”
Section: Resultssupporting
confidence: 64%
“…Microfluidics can provide 2 important advantages in the analysis of cell secretome: (i) small volume limiting dilution of the secreted compounds and (ii) more predictable liquid handling (34,35). Recently, these advantages have been used to enable quantifiable measurements of cell secretions down to a single-cell level (36)(37)(38)(39)(40). However, important challenges remain.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…With the CellCelector it was possible to isolate pure single tumor cells from liquid biopsies of different cancer types including breast , prostate , ovarian , colorectal , and lung cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Should in vitro viability of CTCs be improved, additional live-cell assays could identify (and functionally characterize) candidate single CTCs. For instance, microengraving in an array of subnanoliter wells could be used to evaluate protein secretion from thousands of single cells over ~1–3 hr timescales [43] (i.e. PSA secretion from prostate CTCs) or image cytometry could be used to assess cell motility and single-cell growth kinetics under hypoxic conditions.…”
Section: Improved Recovery Of Candidate Ctcs Without Compromising Seqmentioning
confidence: 99%